La società educante: una rilettura pedagogica dell'Odissea - Bruni, Elsa M. (Studi sulla Formazione/Open Journal of Education, 2014)
The value of the Greek man is measured by his social function: he is considered to be completely at the service of his community. In the same way, the poet, like the philosopher and the orator, plays the role of educator. The case of Homer is significant, in this regard. The most important educator of ancient Greece, Homer turned Achilles into the very ideal of humanness and drew up an educational model which mirrored the aristocratic ethic of archaic Hellenism. This article offers a pedagogical interpretation of The Odyssey retracing the main tenets of the pedagogical awareness which shaped the Western model of education. On this theoretical basis, the author underlines, in the transition from The Iliad to The Odyssey, the importance of Odysseus’s role in the development of a new human and educational ideal – one in which the ancient notion of virility absorbs values pertaining to the hero’s mental and moral traits.